Fijians in Transnational Pentecostal Networks - Brison, Karen J. (Monographs in Anthropology, 2023)
In Fijians in Transnational Pentecostal Networks, Karen J. Brison examines the Harvest Ministry, an independent Fijian Pentecostal church that sends Fijian and Papua New Guinean missionaries to East Africa, Southeast Asia, Europe and elsewhere. After studying the ministry's main church in Suva for several years, Brison visited its missionaries and their local partners in East Africa and Papua New Guinea. The result of those visits, this book provides an unusual insight into Pentecostal churches in the global south, arguing that they seldom produce novel visions of Christianity and world inequality. It also offers new perspectives, by situating Pacific island churches within a global community and by examining social class formation, which is increasingly important in the Pacific. Pentecostalism has a consistent culture all over the world, but shared themes take on different meanings in the face of local concerns. In Fiji, Pentecostal churches are part of middle-class projects constructing leadership roles and highlighting transnational ties for a growing group of indigenous urban professionals. In Papua New Guinea, church leaders promote the idea that youths with blocked aspirations are tough and humble and therefore make invaluable missionaries. In East Africa, Pentecostal churches are part of a networking strategy that entrepreneurial individuals see as essential to survival. As these local groups each use Pentecostalism to advance their own agenda, they endorse Euro-American racial stereotypes and ideologies about social evolution and progress.